WIDTH-WEIGHT AND LENGTH-WEIGHT RELATIONSHIPS IN THREE PORTUNID CRAB SPECIES - PRASAD, P. N.; REEBY, J.; KUSUMA, N; NEELAKANTAN, B (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
Observations on width-weight and length-weight relations of three portunid crab species were made. A precise linearity was observed between catapace measurements and body weight in juveniles adult males and females of three portunids The relationship between width or length and crab weight were highly significant at P - 0.001. The length-weight relationship study assumes an important prerequisite in fishery biological investigations. It is mainly dealt with to know the variations in expected weight from the known length groups which are, inturn, the indications of fatness, breeding and feeding state and their suitability to the environment. The study is also perceived to establish a precise mathematical equation between the length and weight, so that one is measured, the other dimension could be computed. There have been many investigations on length-weight relationship of fin fishes. However, information available on such a study in portunid species is very much fragmentory (Davan et al., 1976; Hamsa, 1978; Chinnamma et al., 1986).